2017
DOI: 10.3892/etm.2017.5365
|View full text |Cite
|
Sign up to set email alerts
|

Rutin inhibits coronary heart disease through ERK1/2 and Akt signaling in a porcine model

Abstract: Abstract.Rutin has a variety of pharmacological actions, including radical reactivity, and protective activity against lipid peroxidation, viruses and acute pancreatitis; thus, it may be used as a treatment for many diseases. The present study aimed to investigate whether rutin inhibits coronary heart disease through extracellular signal-regulated kinase (ERK) 1/2 and Akt signaling in a porcine model. Male Chinese miniature pigs were randomly divided into four groups: A sham group, a coronary heart disease (CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The present study revealed that treatment with rutin after aluminium phosphide toxicity leading to a significant decrease in activity of SOD, with decreased levels of MDA, IL-6, and TNF-α compared to (AlP) intoxicated group but still significantly higher than normal control group, in association with significant increased level of GSH compared to (AlP) intoxicated group but still significantly lower than normal control group. These findings were supported by Lv et al (2018) who demonstrated that treatment with rutin significantly reversed the induced reductions of SOD, CAT, GST and GSH-Px activities in chronic heart disease in the pig. In addition, it has been explained that rutin has an anti-inflammatory activity due to modulation of apoptosis-associated proteins (Aruna et al, 2013).…”
Section: Discussionmentioning
confidence: 58%
“…The present study revealed that treatment with rutin after aluminium phosphide toxicity leading to a significant decrease in activity of SOD, with decreased levels of MDA, IL-6, and TNF-α compared to (AlP) intoxicated group but still significantly higher than normal control group, in association with significant increased level of GSH compared to (AlP) intoxicated group but still significantly lower than normal control group. These findings were supported by Lv et al (2018) who demonstrated that treatment with rutin significantly reversed the induced reductions of SOD, CAT, GST and GSH-Px activities in chronic heart disease in the pig. In addition, it has been explained that rutin has an anti-inflammatory activity due to modulation of apoptosis-associated proteins (Aruna et al, 2013).…”
Section: Discussionmentioning
confidence: 58%
“…TLR-4 and IL-6, in cultured H9C2 cells (Wu et al, 2018). Rutin exhibits similar pharmaceutical functions as that of acacetin (Korkmaz & Kolankaya, 2013;Lv et al, 2018). The pretreatment of rutin in rats dramatically attenuated cyclic guanosine monophosphate (cGMP) and NO level in serum and inhibited inducible nitric oxide synthase (iNOS) and 3nitrotyrosine (3-NT) formation in kidney (Korkmaz and Kolankaya, 2013).…”
Section: Ischemia/reperfusion Injury Protectionmentioning
confidence: 99%
“…Rutin (quercetin‐3‐rutinoside), also known as purple quercetin, vitamin P, sophorin, or rutoside, is a flavonoid which is present in black tea, buckwheat bran, green asparagus, passion flower, berries, and citrus fruits (Lv, Yao, Zhao, & Zhu, 2018; Patel & Patel, 2019; Salvamani et al., 2014). This compound was discovered in 1842 from the plant Fagopyrum esculentum (buckwheat).…”
Section: Treatment Strategies Using Plant‐based Bioactive Compoundsmentioning
confidence: 99%
“…This compound also possesses the activity of anti‐obesity through decreasing the oxidative stress, hepatosteatosis, and dyslipidemia (Mbaveng, Zhao, & Kuete, 2014; Salvamani et al., 2014). This bioactive compound shows positive role for the treatment of cerebrovascular and cardiovascular diseases (Lv et al., 2018). Rutin slows down the development of hypercholesterolemia and prevents atherosclerotic plaque formation in rabbits.…”
Section: Treatment Strategies Using Plant‐based Bioactive Compoundsmentioning
confidence: 99%